Management of Multimedia Learning Media in Early Childhood Education Classes - Luthfy, Perdana Afif; Munawar, Muniroh; Prasetiyawati D.H., Dwi; Karmila, Mila (Universitas Nahdatul Ulama Surabaya, 2025)
This study aims to analyse the management of multimedia learning media in early childhood classes, with the components of planning, development, implementation, evaluation and feedback, maintenance and updating, and training and support. This study uses a survey method with a quantitative approach. The research used a structured questionnaire with closed questions for getting the data distributed to 303 respondents of early childhood teachers. They were analysed using SPSS application. The findings show that in managing multimedia learning tools, most teachers—whether they design their own media or adapt it from other sources—share several common views. First, multimedia planning should be aligned with the learning objectives and context. Second, the development process needs to emphasize student engagement, which involves conducting needs analysis, considering learner characteristics, applying multimedia principles (such as coherence, redundancy, temporal contiguity, and modality), and integrating sound instructional design. Third, the use of multimedia is seen as highly beneficial for students. Fourth, regular evaluation is essential to measure its effectiveness and to give students opportunities to provide feedback. Fifth, teachers must ensure that multimedia content stays relevant and updated in line with current themes. Finally, teachers highlight the importance of adequate training in effective multimedia use, as well as broader support to ensure accessibility, including for students with special needs. The researchers recommend that results of this study be a guideline for teachers in managing multimedia learning media in early childhood classes